Kepribadian Neurotik Tokoh Utama Ryuhei Sasaki dalam Naskah Film Tokyo Sonata Karya Sutradara Kiyoshi Kurosawa - Lubistira, Dwi; Wahyuningsih, Tri Mulyani (Vocational College of Diponegoro University, 2025)
The research is about the neurotic personality of the main character Ryuhei Sasaki in the film script